PEMAHAMAN GURU TENTANG PENILAIAN DALAM KURIKULUM MERDEKA: KASUS DI KABUPATEN BANTUL(TEACHER'S UNDERSTANDING OF ASSESSMENT IN THE MERDEKA CURRICULUM: A CASE IN BANTUL REGENCY) - Sudrajat, Ahmad Kamal; Suyanto, Slamet; Limiansi, Kintan; Aprilisa, Ema; Suratsih, Suratsih; Subiantoro, Agung Wijaya; Nugroho, Ahmad Iskak (Jurnal Edukasi Biologi, 2025)
Changes in social and technological aspects demand curriculum changes in education. Curriculum changes were made to create capable human beings according to the era. The Indonesian Ministry of Education has responded to these changes by implementing the "Merdeka Curriculum". However, there are still some challenges in practice, especially in learning assessment. This study aims to determine teachers' understanding of assessments under the Merdeka Curriculum. This type of research is descriptive, using a qualitative approach. A total of ten biology teachers participated in this study. The results showed that the teacher understood the assessment concept and the steps for compiling assessments under the Merdeka Curriculum. However, from the results of the analysis of the assessment questions used by the teacher, there are still questions that are not following the objectives of the Merdeka Curriculum. The results of this study can be used as a consideration by stakeholders and universities where there is a teacher training program in the process of socialising the Merdeka Curriculum.